Taguchi optimized wear and self-lubricating properties of Al-alloy composite reinforced with hybrid B4C–MoS2 particulates - Kumar, Neeraj; Sharma, Ashutosh; Manoj, M. K.; Ahn, Byungmin (Journal of Materials Research and Technology, 2024)
We investigated self-lubricating Al–Mg–Si hybrid metal matrix composites (HMMCs) embedded with MoS2–B4C particulates, for use in automotive engine components. Composites with different B4C content (x = 3.5, 7.0, 10.5, 14.0, and 17 wt%) were prepared, with the MoS2 content of 3.0 wt%. The metal matrix composites were processed using the powder metallurgy route comprising milling for 2 h and cold pressing and consolidation at a sintering temperature of 560 °C. Their dry sliding wear behavior was examined at applied loads (20–50 N) and sliding distances (1–3 km), and the wear variables were optimized using the Taguchi model (L9). Microstructural analysis was performed using a scanning electron microscope equipped with an energy dispersive spectrometer. A homogeneous particle distribution was observed in the HMMCs, without any appreciable instance of agglomerates. The wear resistance and friction coefficient (COF) improved when MoS2 was incorporated into the HMMCs, compared with a matrix alloy under the same operating conditions. In particular, the COF fluctuated up to a sliding distance of 250 m and was constant for larger values. The wear rate depends on not only the maximum hardness but also the appreciation of self-lubricant MoS2. The Taguchi findings showed that the fraction of hybrid reinforcement had the strongest effect on the wear resistance, and it was followed by the applied load, sliding distance, and track diameter. Apart from providing self-lubrication, the MoS2 particles reduced the wear rate.
Keywords: Al-alloy; Applied loads; Hybrid metal matrix composites; Hybrid MMC; Particulates; Properties of Al; Self-lubricating properties; Sliding distances; Taguchi; Wear-rate; B4C; Hybrid MMC; MoS2; Powder metallurgy; Taguchi; Tribology